The Role of Religious Leaders in Resolving Ulayat Land Disputes - Zonti, Trilara (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
The background to this research problem is that there is a dispute over ulayat land that occurred in Nagari Gadut, Tilatang Kamang District. So the role of religious figures was found in resolving the customary land dispute that occurred in Nagari Gadut. This research aims to see the role of religious figures in resolving customary land disputes in Nagati Gadut, Tilatang Kamang District. The type of research used is descriptive qualitative research methods using data collection techniques, interviews, observation and documentation. The results of the research show that there are disputes over customary land in Nagari Gadut, Tilatang Kamang District. The form of dispute that occurs between the plaintiff and the defendant. The plaintiff did not accept the defendant's desire for private ownership of customary land. Disputes lead to the severing of the relationship between the plaintiff and the defendant, the severing of relationships extending to children, grandchildren, relatives. So the plaintiff reported it to a religious figure to help resolve the dispute that occurred so that the relationship between members of the ethnic group could be resolved. Religious figures as judges in the form of disputes that occurred in Nagari Gadut. The roles of religious figures in resolving customary land disputes are: 1. Role as facilitator 2. Role as mediator, 3. Religious figure as mediator 4. Religious figure as advisor.